Routes of asbestos exposure and the development of mesothelioma in an English region. Issue 6 (June 1997) - Howel, D; Arblaster, L; Swinburne, L; Schweiger, M; Renvoize, E; Hatton, P
Abstract : OBJECTIVES: To investigate the contribution of exposure to asbestos through different routes in the development of mesothelioma. METHODS: Case-control study. 185 confirmed cases of mesothelioma and 160 controls were identified, when death had occurred between 1979 and 1991 in four health districts in Yorkshire. The surviving relatives were interviewed to ascertain lifetime exposure to asbestos. Adjusted odds ratios (ORs) of exposure to asbestos (through occupational, paraoccupational, and residential routes) were calculated for cases and were compared with controls. RESULTS: Likely or possible occupational exposure to asbestos was more common in cases than in controls (OR 5.6, 95% confidence interval (95% CI) 3.1 to 10.1). After excluding those with likely or possible occupational exposure, likely or possible paraoccupational exposure was more common in cases than controls (OR 5.8, 95% CI 1.8 to 19.2). Only six cases of mesothelioma were identified as being solely exposed to asbestos through their residence, compared with nine controls. The OR for residential exposure to asbestos varied between 1.5 and 6.6, depending on which potential industrial sources were included, but the 95% CIs were so wide that slightly reduced or greatly increased odds comparing cases with controls could not be excluded. CONCLUSION: Study results support previous evidence that occupational and paraoccupational exposure to asbestos is associated with developing mesothelioma. Despite a rigorous search, purely residential exposure seemed to account for only 3% of identified cases. No firm conclusion can be drawn about the risks from residential exposure alone, as many of the study subjects could also have been occupationally or paraoccupationally exposed to asbestos.